Actinarctus doryphorus (Tanarctidae) DNA barcodes and phylogenetic reinvestigation of Arthrotardigrada with new A. doryphorus and Echiniscoididae sequences - Grollmann, Milena Marie; Jørgensen, Aslak; Møbjerg, Nadja (Zootaxa, 2023)
Little is still known about the diversity and evolution of marine arthrotardigrades, as they are generally difficult to sample, resulting in a limited amount of molecular data for barcoding and phylogenetic studies. With the current study, we provide the first investigation into COI haplotype diversity in a marine tanarctid and at the same time readdress arthrotardigrade phylogeny. Specifically, we provide COI mtDNA, 18S and 28S rDNA sequences from a population of Actinarctus doryphorus (Tanarctidae) sampled off the coast of Roscoff, France and further provide new 18S sequences from two marine echiniscoidids. A. doryphorus COI sequences confirmed the presence of a single species and further revealed five haplotypes shared among nine sequenced individuals. Our 18S and 28S rDNA datasets were individually and combined analysed with Bayesian inference and Maximum Likelihood. Actinarctus doryphorus was placed together with Tanarctus sequences within a maximally supported Tanarctidae, confirming previous interpretations that the clade is distinct from Halechiniscidae. Although several studies in recent decades have concluded that the marine arthrotardigrades are paraphyletic, recent studies have argued that the clade may not be paraphyletic. Our phylogenetic analyses consistently inferred Arthrotardigrada as paraphyletic, as the clade includes the monophyletic Echiniscoidea. Accordingly, we propose that it is time to suppress the order Arthrotardigrada as it clearly does not reflect tardigrade phylogeny.